2019
DOI: 10.1007/s12032-019-1316-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver graft rejection following immune checkpoint inhibitors treatment: a review

Abstract: Immune checkpoint inhibitors (ICIs) have demonstrated remarkable efficacy in a variety of solid tumors; nonetheless, they have not been well investigated and are still recognized as a relative contraindication for patients with a liver transplantation (LT) history, since ICIs treatment might potentially lead to graft rejection. The program death-1 (PD-1) and the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) pathways are implicated in the tolerance of transplanted organ, as well as blockade of the pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 79 publications
1
28
0
1
Order By: Relevance
“…Dorn et al have reported that, the PD-L1 level is upregulated within primary human hepatocytes using the hepatocellular lipid accumulation model in vitro, while it is confirmed through human liver specimen analysis that, PD-1 and PD-L1 levels are upregulated among NASH cases, which emphasizes the potential effect of aberrant lipid metabolism on immune checkpoint expression. 41 More importantly, such findings indicate that, immune checkpoint antibody treatments, such as nivolumab (anti-PD1 antibody) and ipilimumab (anti-CTLA-4 antibody), 42 will bring more therapeutic benefit to the high-risk HCC cases than to low-risk counterparts, thus leading to superior outcomes. As for the treatments of high-risk patients from lipid metabolic reprogramming, fibronectin type III domain-containing 5 has been illustrated to increase FAO and autophagy of hepatocytes through AMPK/mTORC1 signaling pathway, to reduce de novo synthesis of lipid, thereby alleviating damage.…”
Section: F I G U R Ementioning
confidence: 99%
“…Dorn et al have reported that, the PD-L1 level is upregulated within primary human hepatocytes using the hepatocellular lipid accumulation model in vitro, while it is confirmed through human liver specimen analysis that, PD-1 and PD-L1 levels are upregulated among NASH cases, which emphasizes the potential effect of aberrant lipid metabolism on immune checkpoint expression. 41 More importantly, such findings indicate that, immune checkpoint antibody treatments, such as nivolumab (anti-PD1 antibody) and ipilimumab (anti-CTLA-4 antibody), 42 will bring more therapeutic benefit to the high-risk HCC cases than to low-risk counterparts, thus leading to superior outcomes. As for the treatments of high-risk patients from lipid metabolic reprogramming, fibronectin type III domain-containing 5 has been illustrated to increase FAO and autophagy of hepatocytes through AMPK/mTORC1 signaling pathway, to reduce de novo synthesis of lipid, thereby alleviating damage.…”
Section: F I G U R Ementioning
confidence: 99%
“…On the other hand, great attention has been paid to the development of immunotherapy to treat the solid tumors within the tumor immune microenvironment (TIME). Several immune-checkpoint inhibitors (ICIs), including anti-PD1 ligand (anti-PD-L1), antiprogrammed death-1 (anti-PD1), as well as anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) monoclonal antibodies, 7 present favorable prognostic outcomes in selected advanced HCC cases. Besides, the interaction of tumor cells with the immune microenvironment components has been demonstrated as a key factor for HCC evolution as well as the possible immunotherapy response.…”
Section: Introductionmentioning
confidence: 99%
“…116 Use of immunotherapy and checkpoint inhibitors, although showing some promise, has not been encouraged in transplant recipients due to several reports of severe rejection and a high percentage of graft loss. 118 The mechanism of rejection remains unclear but is thought to be caused by activation of cellular immunity via CD8+ effector cells and downregulation of T-helper cells. There is also concern that immunosuppression may interfere with the efficacy of checkpoint inhibitors since they rely on an intact T cell response.…”
Section: Treatment Of Recurrence After Transplantationmentioning
confidence: 99%